1982
DOI: 10.1080/03079458208436110
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and viral agents associated with tenosynovitis in broiler breeders in Western Australia

Abstract: SUMMARYThe pathology and infectious agents associated with several outbreaks of clinical tenosynovitis in poultry were investigated. Staphylococcus aureus were recovered from tendon tissue of from 51.9% to 97.8% of affected chickens in different outbreaks of the disease. 5. aureus were also present in the liver and heart blood and were considered to contribute to the high mortality observed following occurrence of clinical tenosynovitis in individual chickens. Bacteria otherthan S. aureus were also recovered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Histological lesions in tendons, intertarsal joints and bones were seen where bacteria were isolated; no lesions were observed where the tissues were negative on culture. The lesions in tendon sheaths and tendons and in the intertarsal joints were indistinguishable from natural cases of tenosynovitis reported previously (Kibenge et al, 1982a), the tendon sheaths were thickened by hyperplastic synoviocytes and heterophilic infiltration, and there was bacterial embolism in the metaphysis and necrosis of articular cartilage of the long bones examined.…”
Section: Staphylococcal Countsmentioning
confidence: 50%
See 4 more Smart Citations
“…Histological lesions in tendons, intertarsal joints and bones were seen where bacteria were isolated; no lesions were observed where the tissues were negative on culture. The lesions in tendon sheaths and tendons and in the intertarsal joints were indistinguishable from natural cases of tenosynovitis reported previously (Kibenge et al, 1982a), the tendon sheaths were thickened by hyperplastic synoviocytes and heterophilic infiltration, and there was bacterial embolism in the metaphysis and necrosis of articular cartilage of the long bones examined.…”
Section: Staphylococcal Countsmentioning
confidence: 50%
“…In naturally occurring tenosynovitis it has been suggested that early reovirus-induced tendon damage contributes to the colonisation of S. aureus in tendon tissue (MacKenzie and Bains, 1977;MacDonald et al, 1978;Kibenge et al, 1982a). The pathogenesis of the disease experimentally produced with S. aureus would suggest that S. aureus alone does not result in primary colonisation of tendon tissue, and supports the secondary nature of S. aureus infection following primary reovirusinduced tendon damage.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations